The performativity of multicultural discourses: youth, conflict and contradictions - Maude, Martin (Social Anthropology, 2024)
The Rainbow Nation discourse in South Africa is meant to create a liberatory myth that unites the nation in its cultural and racial differences. However, discourses of multiculturalism are translated, as well as performed, differently within and between various levels of society. The thesis looks at how Rainbow Nation ideals are appropriated by the Non Governmental Organization City at Peace, as well as the young people involved in the City at Peace programme. Ideas about culture and race are negotiated and performed differently because both these terms have shifting meanings depending on context. Race, for example, is often conflated with culture in multicultural ideology (Gunew 1997: 23), but race actually informs class in lived South African realities (Mbola 2008; Kindon and Knight 2004; Dolby 2001). And yet, people may adhere both to 'race as culture' and 'race as class' through different performances pertaining to context. Drawing on Judith Butler (1990), the thesis looks at different levels of performativity of multicultural discourses that reiterate what I call the 'culture'/ 'race' complex, or the assumption that cultural/racial differences are root causes of conflict in South Africa today. The 'culture'/ 'race' complex overlooks how class and gender relations also contribute to tensions and abuse in the country. The thesis argues that misdiagnosing the root causes of conflict in South Africa also leads to a misunderstanding of appropriate conflict-resolution strategies. Many young people in South Africa see themselves as active agents in the making of a 'new' South Africa, and subscribe to Rainbow Nation ideals. However, while Rainbow Nation ideals may provide something to hope for, it is crucial that hope also instigates appropriate action for change. The 'culture'/ 'race' complex suggests that cultural/racial differences need to be overcome to better the country; the thesis argues that tensions and abuse in South Africa are both interpersonal and structural, and must include gender and class in consideration of how difference leads to conflict.